Prevalence and predictors of metabolic syndrome with comparison of myoinositol and metformin in PCOS women - Modak, Rupali; Biswas, Dilip Kumar; Pal, Amitava; Mandal, Tapan Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The objective is to determine the prevalence of metabolic syndrome (MBS) and the effects of insulin sensitizers to improve the clinical and hormonal milieu for better reproductive outcome in PCOS women. Methods: This prospective cross-sectional study was conducted on 50 PCOS women and 50 age matched control to determine the prevalence of the MBS in two tertiary hospitals over one year. Diagnosis of PCOS was based on at least two of ESHRE/ASRM criteria and diagnosis of MBS was based on at least three of NCEPATPIII criteria. Patients already diagnosed as PCOS were treated with insulin sensitizers myoionositol and metformin which were compared. Results: The study revealed that the prevalence of MBS was 40 % (20/50) nearly 4-fold higher than that of control groups. Among PCOS women, the most prevalent MBS factors were high BMI (52%) and low serum HDL-C (42%). The least prevalent factor was high fasting serum glucose level (16%). The resumption of spontaneous regular menstrual cycle and pregnancy rate in infertile groups of PCOS patients with myoionositol and metformin were 61% vs. 26% and 50% vs.91% respectively. The myoionositol group did not require any extra ovulating agents for pregnancy, while 7 out of 11 patients in metfromin group needed clomiphen citrate for ovulation induction to achieve pregnancy. With myoinositol there is significant reduction of weight, BMI, LH/FSH ratio and fasting insulin level; whereas metformin shows decrement of weight and BMI only. Conclusions: The prevalence of MBS in PCOS is nearly 4 times in present study and there is significant improvement of symptom profile, weight, BMI and change of hormonal pattern in myoinositol group.